Manajemen Konflik Negara terhadap Masyarakat Multikultural: Kasus Komunitas Muslim Australia - M. Amin Nurdin (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2005)
The diverse cultural, ethnic, and religious social reality of the Australian population, as a consequence of the open immigration policy in the 1960s, has prompted the Australian government to engage in social and political engineering by adopting multiculturalism as a state ideology. This policy aims to mitigate conflicting values and norms among the white population on one side and immigrants on the other. Australia seems to have successfully managed various conflicts, indicated by the low potential for political, ethnic, and religious violence, including terrorism, compared to other countries, especially its neighbors. The implications of multiculturalism are also evident in the development of the Australian Muslim community, as well as other ethnic and religious communities, which have preserved their cultural heritage and continue to thrive today, albeit still suspected of having potential conflicts.